A multidimensional strategy to managing dysfunctional breathing and exercise-induced laryngeal obstruction in adolescent athletes - Kolnes, L.-J.; Stensrud, T.; Andersen, O. K. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background Exercise induced laryngeal obstruction (EILO) causes inspiratory distress in the upper airway in many adolescent athletes. The nature of EILO is not fully understood, and effective management strategies are lacking. This study aimed to assess the effectiveness of a multidimensional individually tailored intervention, including Norwegian Psychomotor Physiotherapy (NPMP), elements of cognitive behavioural therapy and a rehabilitation plan, in reducing inspiratory distress and dysfunctional breathing in adolescent athletes with EILO.